K. J. Carlson and D. Marchi (eds.). Reconstructing mobility: environmental, behavioral, and morphological determinants - María Alejandra Acosta (Maguaré, 2014)
K. J. Carlson and D. Marchi (eds.). Reconstructing mobility: environmental, behavioral, and morphological determinants. New York: Springer Science. 2014. 295 páginas.